Design of CMOS Differential Transimpedance Amplifier - Charlamov, Jevgenij; Navickas, Romualdas (Elektronika ir Elektrotechnika, 2015)
This paper explores the design of a differential transimpedance amplifier (TIA) integrated circuit for use in optical time domain reflectometer (OTDR) optical receivers (OR). All dependences between primary TIA design variables including OTDR laser pulse width, OR bandwidth, and TIA feedback resistance, are defined. Then, based on these dependencies, it is shown analytically that to achieve a stable system with no overshoots, the open-loop bandwidth of the fully differential amplifier (FDA) at the core of the TIA must exceed closed-loop TIA bandwidth by a factor of at least four. According to equations that are provided, it is shown that minimum amplifier noise occurs when detector and input transistor parasitic capacitances are equal. Schematics and short descriptions of all important TIA components, including the FDA and beta multiplier-based bias circuits, are given. The FDA has a bandwidth of 900 MHz. With a feedback resistance value of 20 kΩ the TIA has a closed-loop bandwidth of 125 MHz. TIA power consumption does not exceed 15 mW and at low bandwidths a variable feedback resistance allows the FDA to achieve up to 7 dB higher dynamic range. The area of the TIA integrated circuit is 100 µm × 250 µm excluding contact pads.DOI: http://dx.doi.org/10.5755/j01.eee.21.1.4548